The psychology of vegetarianism: Recent advances and future directions. (1st December 2018) - Rosenfeld, Daniel L.
Abstract: Whereas vegetarianism has long garnered attention from nutritional science and philosophy, psychological research exploring this eating behavior has emerged only in the past few decades. Six years ago, Ruby (2012) reviewed the extant literature on the psychology of vegetarianism, showcasing its promise as "a blossoming field of study." In the time since, this line of research truly has blossomed, as subsequent work has addressed prior knowledge gaps and initiated new lines of inquiry. While evidence on previously studied topics of dietary motivation, moral values, gender, differences between vegetarians and vegans, barriers to dietary change, and disordered eating has continued to expand, new lines of research on identity, social experiences, flexitarianism, culture, and prospective vegetarianism have emerged. Recent psychometric advancements, moreover, have constructed useful measures to assess relevant constructs. The current review synthesizes this amalgam of research, identifying emergent themes and highlighting promising directions for future inquiry.